1999
DOI: 10.1002/hep.510300236
|View full text |Cite
|
Sign up to set email alerts
|

MMP2 activation by collagen I and concanavalin A in cultured human hepatic stellate cells

Abstract: Fibrosis occurs in most chronic liver injuries and results from changes in the balance between synthesis and degradation of extracellular matrix components. In fibrotic livers, there is a markedly increased activity of matrix metalloproteinase 2 (MMP2), a major enzyme involved in extracellular matrix remodeling. We have previously shown that hepatic stellate cells secrete latent MMP2 and that MMP2 activation occurs in coculture of hepatic stellate cells and hepatocytes concomitantly with matrix deposition. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
86
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 44 publications
(49 reference statements)
8
86
0
6
Order By: Relevance
“…This positive feedback loop has been implicated in previous studies and suggests a role for MMPs in HSC proliferation. 36,37 Such a mechanism could explain why HSC proliferation was suppressed in the BDL livers of the MMP-13Ϫ/Ϫ mice, as assessed by desmin immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…This positive feedback loop has been implicated in previous studies and suggests a role for MMPs in HSC proliferation. 36,37 Such a mechanism could explain why HSC proliferation was suppressed in the BDL livers of the MMP-13Ϫ/Ϫ mice, as assessed by desmin immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…First, we and others have shown that MMP2 activation depends on collagen I deposition in hepatic stellate cell cultures. 17,39 Second, the efficacy of 3-dimensional gels over coating of dishes with collagen I was reported, suggesting that fibrillar collagen organization is crucial in MMP2 activation. Interestingly, an enhanced expression of lysyl oxidase, the enzyme that initiates the first step of extracellular collagen cross-linking, was shown in early stages of liver fibrosis 40 and was suggested to play a role in the early host defense mechanisms in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that extracellular matrix deposition induces activation of the pro-MMP2, secreted by human activated hepatic stellate cell cultures, 15 this process being related to collagen I. 17 The role of collagen I in promoting MMP2 activation, as well as its capacity to favor mesenchymal cell proliferation were shown in several other cell culture systems. [18][19][20] Thus, focalized MMP2 activity on the cell surface appears modulated by the pericellular microenvironment and might facilitate tumor progression and metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 The probes for albumin, collagen IV, laminin ␥1, ␣-smooth muscle actin (␣-SMA), matrix metalloproteinase-2, and 18S ribosomal RNA have been described. 6,13 Anti-a-SMA 14 16 Specimens were routinely processed for histology, i.e., hematoxylin-eosin-saffran and Sirius red staining.…”
mentioning
confidence: 99%